2003
DOI: 10.1002/ptr.1290
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antimicrobial activity of Achillea clavennae L. essential oil

Abstract: The volatile constituents of Achillea clavennae L. (Asteraceae), rare plant of Europe, have been analysed using GC/MS. Twenty- five components making up 81.6% of the oil were characterized with camphor (29.5%), myrcene (5.5%), 1,8-cineole (5.3%), beta-caryophyllene (5.1%) and linalool (4.9%) being the major constituents. The essential oil was evaluated for antibacterial and antifungal activities. The screening of the antimicrobial activity of essential oil was conducted by a disc diffusion test against Gram-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 19 publications
1
56
0
4
Order By: Relevance
“…However, in this study, the Gram-positive bacteria were found to be more susceptible to the L. lucidum flower oil than Gram-negative bacteria. The hydrophilic cell wall structure of Gram-negative bacteria is constituted essentially of lipo-polysaccharide that blocks the penetration of hydrophobic components and avoids the accumulation of essential oils in target cell membrane (Bezic et al, 2003). The single membrane of Gram-positive bacteria is considerably more accessible to permeation by hydrophilic components of essential oil in the target sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the Gram-positive bacteria were found to be more susceptible to the L. lucidum flower oil than Gram-negative bacteria. The hydrophilic cell wall structure of Gram-negative bacteria is constituted essentially of lipo-polysaccharide that blocks the penetration of hydrophobic components and avoids the accumulation of essential oils in target cell membrane (Bezic et al, 2003). The single membrane of Gram-positive bacteria is considerably more accessible to permeation by hydrophilic components of essential oil in the target sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the Gram positive bacteria were found to be more susceptible to the G. biloba leaf essential oil than Gram negative bacteria. The hydrophilic cell wall structure of Gram negative bacteria is constituted essentially of lipo-polysaccharide that blocks the penetration of hydrophobic components and avoids the accumulation of essential oils in target cell membrane (Bezic et al, 2003). The single membrane of Gram positive bacteria is considerably more acessible to permeation by hydrophilic components of essential oil in the target sites.…”
Section: Discussionmentioning
confidence: 99%
“…fumigatus (Bezic et al, 2003;Bekhechi et al, 2011;Falconieri et al, 2011), A. niger (Bezic et al, 2003;Ristic et al, 2004;Stojanovic et al, 2005;Falconieri et al, 2011), C. albicans (Barel et al, 1991;Magiatis et al, 2002;Unlu et al, 2002;Bezic et al, 2003;Candan et al, 2003;Sokmen et al, 2003;El-Shazly et al, 2004;Sokmen et al, 2004;Stojanovic et al, 2005;Tuberoso et al, 2005;Iscan et al, 2006;Bader et al, 2007;Karamenderes et al, 2007;Maggi et al, 2009;Turkoglu et al, 2010;Falconieri et al, 2011;Kucukbay et al, 2011;Radulovic et al, 2012;Albayrak, 2013;Kazemi and Rostami, 2015;Turkmenoglu et al, 2015;Fahed et al, 2016), C. glabrata (Magiatis et al, 2002;Al-Snafi, 2013), C. krusei (Candan et al, 2003;Sokmen et al, 2003;Falconieri et al, 2011;Turkmenoglu et al, 2015), C. herbarum (Bekhechi et al, 2011), C. kefyr (Ghasemi et al, 2008), C. krusei (Candan et al, 2003;Sokmen et al, 2003;Falconieri et al, 2011;Turkmeno...…”
Section: Antifungal Activitiesmentioning
confidence: 99%